Senescence of activated stellate cells limits liver fibrosis - Krizhanovsky, Valery (2008)
Cellular senescence acts as a potent mechanism of tumor suppression; however, its functional contribution to non-cancer pathologies has not been examined. Here we show that senescent cells accumulate in murine livers treated to produce fibrosis, a precursor pathology to cirrhosis. The senescent cells are derived primarily from activated hepatic stellate cells, which initially proliferate in response to liver damage and produce the extracellular matrix deposited in the fibrotic scar. In mice lacking key senescence regulators, stellate cells continue to proliferate, leading to excessive liver fibrosis. Furthermore, senescent activated stellate cells exhibit gene expression profile consistent with cell cycle exit, reduced secretion of extracellular matrix components, enhanced secretion of extracellular matrix degrading enzymes, and enhanced immune surveillance. Accordingly natural killer cells preferentially kill senescent activated stellate cells in vitro and in vivo, thereby facilitating the resolution of fibrosis. Therefore, the senescence program limits the fibrogenic response to acute tissue damage.